Exchange rate regimes in India: Central bank interventions and purchasing power parity in the context of ASEAN currencies - Angad Siddharth; Constantinos Alexiou; Sofoklis Vogiazas (Economies, 2024)
In this study spanning four decades, we explored the relationship between the Reserve Bank of India's (RBI) interventions and the validity of Purchasing Power Parity (PPP) across two distinct exchange rate regimes: the fixed exchange rate regime (1975-1993) and the managed floating regime (1994-2015). Applying an error correction model (VECM), our analysis reveals that under the fixed exchange rate regime, the environment is conducive to PPP due to frequent interventions by the RBI. However, in the managed floating regime, selective interventions weaken the applicability of PPP. These findings align with prior research but also hint at the limitations of linear models in capturing the intricate dynamics of PPP when central banks are involved. Nonlinear models may hold the key to unraveling the relationship more effectively.
Keywords: E31; F31; F15; C32; 330; ASEAN; central bank interventions; foreign exchange rate; India; purchasing power parity; VECM